2018
DOI: 10.1007/s10753-018-0809-4
|View full text |Cite|
|
Sign up to set email alerts
|

Sam68 Promotes Invasion, Migration, and Proliferation of Fibroblast-like Synoviocytes by Enhancing the NF-κB/P65 Pathway in Rheumatoid Arthritis

Abstract: Src-associated substrate during mitosis of 68 KDa (Sam68), also known as KH domain containing, RNA binding, signal transduction associated 1 (KHDRBS1), is the prototypic member of the signal transduction activator of RNA (STAR) family of RNA-binding proteins. Previous studies have indicated that Sam68 regulates nuclear transcription factor kappa B (NF-κB) to mediate inflammation. In this study, we analyzed the effect and possible mechanisms of Sam68 in rheumatoid arthritis (RA). By western blot analysis and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Lastly, KHDRBS1 is overexpressed in fibroblast-like synoviocytes of patients with RA, wherein it was involved in invasion, migration and proliferation. 50 Conversely, our RA cohort showed a lower expression of KHDRBS1 in the three leucocyte subsets, accompanied by an even lower expression in synovial fluid leucocytes. Nevertheless, in our cohort, an inverse relationship among reduced levels of this splicing factor and both, a higher disease activity and the overexpression of a number of circulating inflammatory mediators was demonstrated, thus supporting its potential involvement in the pathophysiology of RA and pointing to a specific dysregulation in different cells and tissues.…”
Section: Discussionmentioning
confidence: 58%
“…Lastly, KHDRBS1 is overexpressed in fibroblast-like synoviocytes of patients with RA, wherein it was involved in invasion, migration and proliferation. 50 Conversely, our RA cohort showed a lower expression of KHDRBS1 in the three leucocyte subsets, accompanied by an even lower expression in synovial fluid leucocytes. Nevertheless, in our cohort, an inverse relationship among reduced levels of this splicing factor and both, a higher disease activity and the overexpression of a number of circulating inflammatory mediators was demonstrated, thus supporting its potential involvement in the pathophysiology of RA and pointing to a specific dysregulation in different cells and tissues.…”
Section: Discussionmentioning
confidence: 58%
“…The hyperproliferating FLSs release a large number of pro-inflammatory indicators, such as interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α, causing abnormal inflammation in the synovial membrane ( 8 , 9 ). What is more, the activated FLSs release matrix metalloproteinases (MMPs), which promote FLS migration and invasion ( 10 , 11 ). Therefore, reducing the activation and inflammatory response of FLSs is a promising therapeutic strategy for the treatment of RA ( 8 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Western blot and qRT-PCR analyses revealed that inhibition of BMP3 expression using BMP3-RNAi resulted in the overexpression of the proinflammatory cytokines IL-6, IL-1β, and IL-17A in RA and AIA FLS treated with TNF-α. Studies indicate that the secretion of inflammatory factors leads to the activation and migration of RA FLS and exacerbates the inflammatory response [ 30 , 34 ]. Furthermore, inhibition of BMP3 expression using BMP3-RNAi increases the expression of CCL-2, CCL-3, VCAM-1, MMP-3, and MMP-9 in RA and AIA FLS treated with TNF-α, whereas TIMP-1 expression is decreased.…”
Section: Discussionmentioning
confidence: 99%